Uso do leite de vaca no controle do oídio em feijão-de-vagem - Lagos, Frank Silvano (2009)
The rising search for healthier food demands a rising in the production without fertilizers. The bean pod is one of the main plants from the vegetable gardens grown in Brazil. Among the main diseases which affect this culture is the powdery mildew which can cause losses in the production up to 69%, being a common occurrence in protected cultures especially in late periods. The usage of milk has shown good perspectives in this disease control in different cultures. Works with the aim of evaluate the effect of in natura milk and its possible mechanisms of action in the powdery mildew control in bean pods under a protected environment were developed during 2007 and 2008. In the Federal Technological University of Paraná – campus in Pato Branco- PR. The experience was conducted with the application of in natura milk in the concentrations of 0%, 5%, 10%, 15% and 20% every week or every fifteen days with or without the adhesive spreader. The severity of this disease was evaluated as well as the productivity. The design was in blocks at random, with four repetitions. In other experiment it was evaluated the milk chemical components effect with application leaf of Potassium Nitrate (0.79 g L-1), Ammonium Chloride (0.82 g L-1), Calcium Nitrate (0.96 g L-1), Ammonium Phosphate Monobasic (0.51 g L-1), Sodium Carbonate (0.23 g L-1), mixture of these components, milk (200 ml L-1) and water. The design was entirely developed with three repetitions. In the third experiment the metabolic activity was evaluated in the follicular tissue in bean pods treated with weekly applications of cow milk in natura in the concentrations of the first experiment. The cultivation was in vases in a vegetation house with controlled environment. The design was entirely developed with four repetitions. In order to make the biochemical analysis (proteins, total sugar and reductors, peroxidasis e PAL) Follicular disks of 0.2g were collected from each experimental unity, 24, 48 e 72 hours after the application of cow milk in natura. The milk applied weekly promoted the powdery mildew control of 37.94 to 79.96%. Being used every fifteen days the control varied from 22.32 to 28.59%, being more effective in the beginning of the infestation. Its application does not require the usage of adhesive spreader. The most variable concentrations were between 10 e 15%. The application of different chemical components in a combined form controlled the disease in a similar way to the application of cow Milk in natura. The applications of rising concentrations of cow milk in natura interfered in the follicular biochemical patterns of proteins, total sugar and reductors, activity of peroxidasis and PAL demonstrating to be an elicitor which is able to induct to an answer of resistance, alternating the enzymatic activity related to the bean pod defense.